27^2/3 x 27^1/3 x 27^-4/3
Answers
Answered by
1
Step-by-step explanation:
27^2/3 x 27^1/3 x 27^-4/3
27 can be written as 3^3
Therefore,
3^3*2/3 * 3^3*1/3 *3^3*-4/3
(9*3*1)/81
1/4 (ans)
Answered by
2
Step-by-step explanation:
given 27^2/3 x 27^1/3 x 27^-4/3
we know a^m*a^n=a^(m+n)
similarly
27^2/3 x 27^1/3 x 27^-4/3=27^(2/3+1/3-4/3)
=27^(2/3-1)
=27^(-1/3)
=(3^3)^(-1/3)
we know (a^m)^n=a^(m*n)
=>3^(3*-1/3)
=3^(-1)
we know a^(-1)=1/a
so 3^(-1)=1/3
so answer is 1/3
so answer is 1/3 please let me know for. any other quires all the best:)
Similar questions
Math,
5 months ago
Social Sciences,
5 months ago
Political Science,
5 months ago
Geography,
10 months ago
Science,
10 months ago
Math,
1 year ago
Math,
1 year ago